Effectiveness of Homework Assignments and Quiz as Instructional Tools: the Case of Business Finance Courses at Universitas Klabat - Ruhupatty, LeRoy Tim; Oberholster, Braam (JBE (Journal of Business and Economics); Volume 7 No.1, 2008 JBE UNKLAB, 2008)
This paper seeks to find out whether homework and quiz are effective instructional tools in learning process of students enrolled in business finance course at Universitas Klabat. Furthermore, this study aims to find out whether gender and student accommodation has any influence on students academic achievement (student accommodation is segregated into three categories: living in supervised on-campus dormitory; living with university staff; and living off-campus. The sample consists of 452 students enrolled in business finance courses over five semesters over the period 2000 to 2002. The study uses multiple regression analysis with final examination grade as dependent variable with homework assignment grade and average quiz grade as independent variables. Furthermore, the study tests whether gender and student accommodation has any correlation with examination performance using ANOVA. The examination grade is used as a proxy variable for learning. The findings indicate that homework in business finance courses is an effective instructional tool. Quizzes used in business finance courses are an effective feedback tool that can provide instructors with warnings. Differences in examination performance of business finance students are not gender or student accommodation related.